Micronuclei in exfoliated cells: A biomarker of genotoxicity in tobacco users - Meenakshi Upadhyay; Parul Verma; Robin Sabharwal; Santosh Kumar Subudhi; Suruchi Jatol-Tekade; Vihang Naphade; Basanta Kumar Choudhury; Pravudeva Devidutta Sahoo (Nigerian Journal of Surgery, 2019)
Aims: The aim of this study was to analyze the tobacco-related genotoxic effects in individual with habit of smoking and chewing tobacco. Materials and Methods: The present study sample consisted of 120 individuals attending the outpatient department of D. J. College of Dental Sciences and Research, Modinagar, Uttar Pradesh (UP). The sample was divided into four groups as follows: Group I (individuals with habit of smoking tobacco), Group II (individuals with habit of chewing tobacco), Group III (individuals with habit of smoking and chewing tobacco), and Group IV control group (nontobacco-exposed individuals). Patients were asked to rinse their mouth gently with water. The exfoliated cells were obtained by scraping the buccal mucosa of individuals with a wooden spatula. The scraped cells were placed on the precleaned slides. The smears were then stained with RAPID-PAP™ and analyzed under the microscope. Data were analyzed using SPSS statistical software. Results: In the present study, an arbitrary unit was obtained using frequency/day multiplied by the duration of years (risk multiplication factor [RMF], a positive and significant correlation were observed between the RMF and the mean percentage of micronucleated cell count in smokers, chewers, and in individuals with both smoking and chewing habit, respectively. A weak positive and nonsignificant correlation were observed between age and mean percentage of micronucleated cells in smokers and smokers + chewers, respectively, while it was weak negative and nonsignificant in chewers. In control group, correlation between age and percentage of micronucleated cells was weak positive and nonsignificant at 5% level of significance. Conclusion: The micronuclei in exfoliated mucosal cells from buccal mucosa can be used as a biomarker of genotoxicity in predicting the effects of carcinogens.